Pola Integrasi Nilai-Nilai Kepesantrenan dalam Mengimplementasikan Budaya Religi di Universitas Nurul Jadid - Faizin Faizin; Farhah Farhah (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2018)
The uniqueness of universities in Islamic boarding schools Through the curriculum collaboration of Nurul Jadid University strives to produce excellent Islamic boarding school graduates not only in accordance with their respective potentials but also to have a religious understanding that influences such as the literary ability and furudhul's understanding ainiyah. The presence of Tri logi and the five awareness students were able to interpret the leaders, lecturers and students of the University of Nurul Jadid to bring about actual changes in civilization, therefore the researcher discussed the integration of Islamic values the nurul jadid university, to find out the understanding of the Tri logi objectives. and Panca awareness of students, both from leaders, lecturers and students who have never received an education in the Nurul Jadid boarding school. qualitative reception analysis method, with a descriptive-qualitative approach. The research subject was at Nurul Jadid Paiton Probolinggo